Locally or Non-Locally Reacting Boundaries: Does it Make a Significant Acoustic Difference?. Issue 2 (June 2014) - Opdam, Rob; de Vries, Diemer; Vorländer, Michael
As an alternative for the common geometric room acoustical models, a wave theory-based model has been developed derived from the so-called WRW scheme, often used in seismic modelling [1, 2]. In this model, the wave properties of sound are appropriately taken into account. The proposed model is similar to the Boundary Element Method (BEM). Other than in BEM, in the WRW scheme non-locally reacting room boundaries can be included in the modelling process using only the fluid domain. The results of sound field modelling in rooms with locally as well as non-locally reacting boundaries are presented. The differences are analysed and their relevance is discussed.